Caloric test versus video head impulse test in vestibular neuritis patients. (1st January 2021) - Mekki, S.; Mohamed, W.; Omar, S.; Gad, N.
Abstract: Background: The caloric test and the video head impulse test (vHIT) are diagnostic tools to examine vestibular neuritis (VN) patients through assessing the function of the semicircular canals. Both tests assess the vestibular ocular reflex (VOR) with major differences between them as regards stimulus characteristics, frequency, methodology and function examined. The caloric test is the gold standard test in VOR assessment. The vHIT assesses the same reflex (VOR) by using a video-assisted examination of the impulsive manoeuvre. Objectives: The aim of this study was to assess the presence or absence of agreement between both vHIT and the caloric test in VN patients. Design: A case-control study was conducted in Audiovestibular unit, Department of ENT, Zagazig University Hospitals. About 24 patients with VN were included. Both vHIT and the caloric test were done on two consecutive days. We assessed the agreement between these two tests. Results: Horizontal gain asymmetry (GA) with the canal paresis. There was a slight agreement between both tests. Conclusions: The VHIT and the caloric test stimulate different frequencies of VOR. They are complementary rather than being alternatives in the diagnosis of peripheral VN.